Exploring TVET lecturer perceptions about work-integrated learning in South Africa - Joseph Mesuwini; Kgomotlokoa Linda Thaba-Nkadimene; Duduzile Mzindle; Cephas Makwara (Scandinavian Journal of Vocations in Development, 2022)
This paper discusses the perceptions of Technical and Vocational Education and Training (TVET) lecturers’ work-integrated learning (WIL) to determine how they understood their learning in a South African context. This study explored TVET lecturer perceptions about WIL, which is not reported as much in the literature. Eighteen lecturers from the civil, electrical and mechanical trades were involved in the study. A multiple case study design was adopted. The non-probability sampling design, specifically convenience and purposive sampling was used because participants were identified according to the researcher’s judgment. Qualitative data were gathered from TVET lecturers learning through WIL in industry. A thematic analysis model was used to search for common themes and analyse the data. Bergami and Schuller’s industry placement model underpinned the study. Using interviews and non-participant observation provided an opportunity for data triangulation, thereby addressing shortfalls that may be deep-rooted in a single method approach. This provided opportunities to test the trustworthiness and dependability of research findings. It emerged that TVET lecturers gained meaningful and current industry exposure. Lecturers described WIL as a positive and exciting initiative where they learnt from experts who shared valuable industry experiences. A few participants voiced their dissatisfaction over a lack of support from industry personnel. Further studies on challenges experienced by TVET lecturers during WIL are recommended. Overall, WIL complements theory with practice positively. The results may differ if future studies include other disciplines. WIL initiatives could influence different role players aligned to TVET provision.